Improving management of natural resource revenues in Mongolia. (Metro Manila, Philippines Asian Development Bank, 2019)
Mongolia economic fortunes are closely tied to the performance of its major commodities, especially those in the mineral sector. As a result of commodity dependence, the economy is exposed to boom and bust cycles. This policy note draws on the experience of other countries to offer solutions toward a more resilient and sustainable economy. The recommendations focus on strengthening public financial management and policy implementation as well as the need to foster greater economic diversification.
Keywords: Public administration; Sustainable development; Electronic books